Assessing the Effects of COVID-19 on Restaurant Business From Restaurant Owners’ Perspective - Sardar, Sazu; Ray, Rudrendu; Hasan, Md. Kamrul; Chitra, Shital Sohani; Parvez, A. T. M. Shahed; Avi, Md. Ashikur Rahman (Frontiers in Psychology, 2022)
Purpose The main purpose of this study is to assess the effects of COVID-19 on the restaurant businesses of Bangladesh. It examines the socio-economic impacts of the humanitarian disaster of the COVID-19 pandemic from the perspective of restaurant owners. The study also intends to provide recommendations to mitigate effects on the restaurant business. Design/Methodology/Approach A qualitative research approach was adopted to explore the effects of the COVID-19 pandemic on the restaurant businesses of Bangladesh. A total of 22 in-depth interviews were conducted with the top-ranked restaurant owners in the Rajshahi City Corporation area of Bangladesh. Thematic analysis technique was applied for analyzing the collected data. Findings The study found that the restaurant owners were compelled to reduce their number of employees, and forced to ensure social distancing and proper sanitization which increased the expenses. Although online orders and home delivery services have increased significantly, restaurant business operation is gradually turning critical owing to the lack of financial support. Thus, restaurant owners urge the govenrment for financial assistance. Research Limitations/Implications Since this research only focused on one city in Bangladesh, the outcomes of study may have a dearth of generalizability. Hence, the investigators are encouraged to extend the study area. Practical Implications This study will help restaurant owners and policymakers in formulating contemporary business policies and strategies. Thus, it will be supportive of improving the present condition of the restaurant businesses in developing countries like Bangladesh. Originality/Value This paper identified the truculent scenario of the restaurant business during the COVID-19 pandemic.